The Influence of Corporate Social Responsibility on Word of Mouth and Company Value, with Company Reputation as a Mediation Variable: Pengaruh Tanggung Jawab Sosial Perusahaan Terhadap Dari Mulut ke Mulut dan Nilai Perusahaan, dengan Reputasi Perusahaan Sebagai Variabel Mediasi - Anggraini, Titania; Fitriyah, Hadiah (Indonesian Journal of Law and Economics Review, 2022)
This study aims to analyze test empirically : 1) Effect of Corporate Social Responsibility 2) Effect of Corporate Social Responsibility, Word of Mouth (WOM), Company Value with Corporate Reputation as Moderating Variables.This study shows that Corporate Social Responsibility (X1) as independent variables, with and Word of Mouth (Y1) and Company Value (Y2) as dependent variable (Y), and Corporate Reputation as a moderating variables (Z). The population of this study are Aqua consumers Pasuruan region. Sampling technique used in this research is purposive sampling with data is compiled with distribute questionareto Aqua comsumers in Pasuruan region. Analysis technique data used that includes the outer model, inner model and path analysis with Smart PLS 3.2.8 for windows program.The results of this research showed that Corporate Social Responsibility has significant-positively effect on Word of Mouth , and Company Value with Corporate Reputation be able to mediate relationship.